Publisher correction: understanding the genetic complexity of puberty timing across the allele frequency spectrum - Kentistou, Katherine A.; Kaisinger, Lena R.; Stankovic, Stasa; Vaudel, Marc; Mendes de Oliveira, Edson; Messina, Andrea; Walters, Robin; Liu, Xiaoxi; Busch, Alexander S.; Helgason, Hannes; Thompson, Deborah J.; Santoni, Federico; et al. (Nature genetics, 2024)
Pubertal timing varies considerably and is associated with later health outcomes. We performed multi-ancestry genetic analyses on ~800,000 women, identifying 1,080 signals for age at menarche. Collectively, these explained 11% of trait variance in an independent sample. Women at the top and bottom 1% of polygenic risk exhibited ~11 and ~14-fold higher risks of delayed and precocious puberty, respectively. We identified several genes harboring rare loss-of-function variants in ~200,000 women, including variants in ZNF483, which abolished the impact of polygenic risk. Variant-to-gene mapping approaches and mouse gonadotropin-releasing hormone neuron RNA sequencing implicated 665 genes, including an uncharacterized G-protein-coupled receptor, GPR83, which amplified the signaling of MC3R, a key nutritional sensor. Shared signals with menopause timing at genes involved in DNA damage response suggest that the ovarian reserve might signal centrally to trigger puberty. We also highlight body size-dependent and independent mechanisms that potentially link reproductive timing to later life disease.
The Lifelines Cohort Study ; The Danish Blood Donor Study ; The Ovarian Cancer Association Consortium: Jenny Chang-Claude, Ute Hamann ; The Breast Cancer Association Consortium: Hermann Brenner, Frederico Canzian, Jenny Chang-Claude, Ute Hamann ; The Biobank Japan Project, The China Kadoorie Biobank Collaborative Group
Online verfügbar: 09. Juli 2024
Gesehen am 02.05.2025